THE MEANING OF WORK TOWARDS MOTHER WHO HAS AUTISTIC CHILD - Saputra, Anoldy Agus; Karyono, Karyono (Jurnal EMPATI, 2014)
This research was aimed to find out and to comprehend the meaning of work on mother who has autistic child. This research used a qualitative method by using phenomenological approach in specific. The data collecting was accomplished by means of in-depth interview towards three career mothers who have autistic child. The data analysis used in this study was Interpretative Phenomenological Analysis (IPA).The research result indicated that the reason of all subjects to be a career mother although they have autistic child was economic factor, namely for family prosperity and be autonomous in economical aspect. The consequences which were resulted from subjects’ decision who kept working could be minimized due to the support from family and the office policy. The subjects felt the benefit by becoming a career mother, which is fulfilling the needs of autistic child and be autonomous in financial side. However, the other subjects accepted different benefit that is having worthwhile knowledge for society.